Mixed Reality Technology in Total Knee Arthroplasty: An Updated Review With a Preliminary Case Report - Su, Shilong; Lei, Pengfei; Wang, Chenggong; Gao, Fawei; Zhong, Da; Hu, Yihe (Frontiers in Surgery, 2022)
Background Augmented reality and mixed reality have been used to help surgeons perform complex surgeries. With the development of technology, mixed reality (MR) technology has been used to improve the success rate of complex hip arthroplasty due to its unique advantages. At present, there are few reports on the application of MR technology in total knee arthroplasty. We presented a case of total knee arthroplasty with the help of mixed reality technology. Case Presentation We presented a case of a 71-year-old woman who was diagnosed with bilateral knee osteoarthritis with varus deformity, especially on the right side. After admission, the right total knee arthroplasty was performed with the assistance of MR technology. Before the operation, the three-dimensional virtual model of the knee joint of the patient was reconstructed for condition analysis, operation plan formulation, and operation simulation. During the operation, the three-dimensional virtual images of the femur and tibia coincided with the real body of the patient, showing the osteotomy plane designed before the operation, which can accurately guide the completion of osteotomy and prosthesis implantation. Conclusions As far as we know, this is the first report on total knee arthroplasty under the guidance of mixed reality technology.